How to train your dragon / How to be a pirate - Cowell, Cressida (London : Hodder Children's Books, 2010)
Chronicles the adventures and misadventures of Hiccup Horrendous Haddock the Third as he tries to pass the important initiation test of his Viking clan, the Tribe of the Hairy Hooligans, by catching and training a dragon.
U
Originally published in 2003 by Hodder Children's Books in Great Britain"--Page facing title page.
b
b
Keywords: Vikings -- Juvenile fiction; Dragons -- Juvenile fiction; Humorous stories; Vikings -- Fiction; Dragons -- Fiction; Humorous stories; Dragons; Humorous stories; Vikings; Fiction; Juvenile works